Viés Analítico em Estudos Tafonômicos com Macroinvertebrados: Implicações (Paleo)Ambientais e (Paleo)Ecológicas - Rodrigues, Sabrina Coelho; Simões, Marcello Guimarães [UNESP]; Pires-Domingues, Ricardo Angelim (My University, 2009)
A review of recent literature shows that most taphonomic studies of Holocene and fossil macrovertebrates are not methodologically standardized. Hence, results from distinct studies are not comparable, even among researches sharing virtually identical goals, targeting the same biological group of similar age and depositional environment. The effects of the shell size in the taphonomic analysis are still poorly understood. In order to study this issue, the taphonomic signatures (articulation, valve type, fragmentation, abrasion, corrosion, edge modification, color alteration, bioerosion and encrustation) of brachiopod shells (Bouchardia rosea (Mawe)), from Ubatuba Bay in the northern coast of São Paulo State, were investigated according to the sieve sizes. In the study area, 14 collecting stations were sampled via Van Veen grab sampler, along a bathymetric gradient, ranging from 0 to 35 m of depth. Bulk samples were sieved through 8 mm, 6 mm, and 2 mm mesh sizes, yielding a total of 5.204 shells. The results indicate that, when taphonomic signatures were independently analyzed per size classes (8 mm, 6 mm, and 2 mm), the taphonomic signatures are recorded in a complex and random way. Additionally, cluster analysis showed that the similarity among the clusters vary according to the considered sieve size. Thus, the sieve size plays an important role in the distribution of taphonomic signatures in shells of distinct sizes. These results suggest that the concentration of the taphonomic analysis on one class (e.g., the largest sieve size, 8 mm) is not always the best method. Rather, the total data (all sieves included) seems more accurate in recording the whole spectrum of taphonomic processes recorded in shells of a given assemblage.
Analytical bias in taphonomic studies of macro-invertebrates: (paleo)environmental and (paleo)ecological implications.